Comparative analysis of the production risk of major fruit species - Persely, Sz. (International Journal of Horticultural Science, 2009)
Hungary possesses excellent agri-ecological potentials even in an international comparison. Despite their decreasing economic weight, agriculture and food production are of great significance, since the supply of the population with high quality and inexpensive food is a fundamental social demand and one of the essentials of the quality of life. The development of vegetable and food production is of great importance both from the aspect of healthy nutrition and comparative advantages (cheap workforce, professional expertise, traditions of production, climate favourable for quality). Within the Hungarian fruit production apple and sour cherry are essential branches in virtue of their significance. It is widely known, that – though to a different extent in the case of certain fruit varieties – satisfaction of the need for appropriate habitat is one of the important conditions of a decent quality and secure production. In my research, I analyse the territorial distribution, production standard and production risk of the Hungarian apple and sour cherry branches. I did not have the opportunity – because of the imperfections of the database – to compare long time series, therefore I examine the random effects affecting production by using the data of 3 years (they have the same content). I ranked and assessed each habitat and the production risks of certain fruit species compared to each other on the basis of indexes of relative deviation.